Effect of lyophilization on HRP–antibody conjugation: an enhanced antibody labeling technology - Saikant Regidi; Shilpa Ravindran; Ashitha L. Vijayan; Vani Maya; Lakshmi Sreedharan; Jeslin Varghese; Kartik Ramaswami; Manoj Gopi (BMC Research Notes, 2018)
Abstract Objective Immunoassay usually deal with the antibody labeling with various reporter molecules, one such useful reporter molecule is horseradish peroxidase (HRPO). Conjugating enzyme with antibody without losing its enzymatic activity is a challenging task. Our aim is to modify existing classical method of conjugating antibodies with HRP to enhance immunoassay techniques with better sensitivity. We used chemicals such as sodium meta periodate to generate aldehyde group by oxidation of carbohydrate moieties on HRPO. The activated form of HRPO is lyophilized and then mixed with 1 mg/ml concentration of antibodies to be conjugate. Results After confirming chemical modification of conjugates via UV-Spec and SDS-PAGE independent molecules were used for conjugation and HRP–antibody conjugate. Finally, enzymatic activity of HRP–antibody conjugate was confirmed by performing direct ELISA. Functional properties were analyzed using ELISA with dilution of 1:5000, whereas the conjugate prepared by existing method of conjugation worked with as low dilution of 1:25 with a p value highly significant (< 0.001) for classical verses modified method of conjugation preparation. Collectively, this study showed the enhanced ability of antibody to bind more number of HRPO with an additional step of lyophilization in the regular conjugation protocol. Future exploration are necessary on wide range of IgG antibodies.